2011
DOI: 10.1001/jama.2011.826
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 23 and Risks of Mortality and End-Stage Renal Disease in Patients With Chronic Kidney Disease

Abstract: Context High levels of the phosphate regulating hormone, fibroblast growth factor 23 (FGF23), associate with mortality in patients with end-stage renal disease (ESRD), but little is known about its relationship with adverse outcomes in the much larger population of patients with earlier stages of chronic kidney disease (CKD). Objective Evaluate FGF23 as a risk factor for adverse outcomes in patients with CKD. Design, Setting and Participants A prospective study of 3,879 participants with CKD stages 2 – 4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
720
7
15

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 924 publications
(798 citation statements)
references
References 32 publications
31
720
7
15
Order By: Relevance
“…FGF‐23 predicts the progression of CKD in human patients,13, 27, 28 and FGF‐23 concentrations are also well established as being independently associated with case fatality in CKD patients at the start of hemodialysis,14, 29 and in earlier stages of CKD 27, 28. At present, just as has been debated for many years concerning PTH, it is unclear whether FGF‐23 is a uremic toxin, or whether it is a surrogate marker for other causes of uremic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…FGF‐23 predicts the progression of CKD in human patients,13, 27, 28 and FGF‐23 concentrations are also well established as being independently associated with case fatality in CKD patients at the start of hemodialysis,14, 29 and in earlier stages of CKD 27, 28. At present, just as has been debated for many years concerning PTH, it is unclear whether FGF‐23 is a uremic toxin, or whether it is a surrogate marker for other causes of uremic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 Several cohort studies have examined the relationship between FGF-23 and renal outcomes. [10][11][12][13][14][15] In line with findings in the Chronic Renal Insufficiency Cohort cohort 11 and in the MMKD study 10 from analyses not considering the FGF-23-ADMA interaction, we confirmed that the FGF-23-CKD progression relationship was independent of (1) classic risk factors and (2) CKD-specific risk factors, such as proteinuria and the GFR, that are known to belong to the strongest predictors of CKD progression, as well as (3) major biomarkers of CKD mineral and bone disorder, including serum phosphate, 1,25(OH) 2 D, and PTH. These results further highlight the potential relevance of FGF-23 as a novel risk factor for evolution toward kidney failure in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…in the United States, [11][12][13][14] as well as a large study in transplant recipients in Hungary, 15 have coherently associated high plasma FGF-23 with CKD progression toward kidney failure.…”
mentioning
confidence: 94%
“…A promising CKD biomarker is fibroblast growth factor 23 (FGF-23), which is highly increased in CKD patients and associated with cardiovascular disease and mortality (380)(381)(382). Other potentially interesting molecules include the tubular injury markers NGAL (383-385), KIM-1 (385-388), TIMP-2 (389), IGFBP7 (389) and liver-type fatty acid-binding protein (L-FABP) (390,391).…”
Section: Serum and Urine Biomarkersmentioning
confidence: 99%